(untitled) - Will Forsyth (London, 1996)
This book is divised into three sections: reading, speaking and words and phrases which can follow one another immediately or be spread over two lessons and a homwork session. The vocabulary exercises can be used either for pre-teaching before the texts are read, or as a vocabulary review before the speaking activities or as a final revision
Keywords: english language - study and teaching